The Impact of c‐Fos/Activator Protein‐1 Inhibition on Allogeneic Pancreatic Islet Transplantation. Issue 10 (26th May 2015) - Yoshida, T.; Yamashita, K.; Watanabe, M.; Koshizuka, Y.; Kuraya, D.; Ogura, M.; Asahi, Y.; Ono, H.; Emoto, S.; Mizukami, T.; Kobayashi, N.; Shibasaki, S.; et al.
Abstract : Unpreventable allograft rejection is one of the main problems in pancreatic islet transplantation (PIT). Therefore, it is imperative to develop a more effective immunosuppressive strategy. The blockade of transcription factors has been a central part of T cell–depleting immunosuppressive therapies, as typified by the use of calcineurin inhibitors. The inhibition of activator protein‐1 (AP‐1) offers a novel strategy for immunosuppression in PIT, although to date, no reports on the effects of AP‐1 inhibition are available. In this study, we investigated the immunosuppressive effects of T‐5224, a c‐Fos/AP‐1‐selective inhibitor, on murine T cells activated by αCD3+αCD28 mAbs. T‐5224 inhibited proliferation, CD25 up‐regulation, and the production of IL‐2 and interferon‐γ. In addition, T‐5224 blocked the nuclear translocation of c‐Fos/AP‐1 in activated murine T cells. In BALB/c (H‐2 d )‐to‐C57BL/6J (H‐2 b ) mouse PIT, the 2‐week administration of T‐5224 prolonged survival of 600 islet allografts in a dose‐dependent manner. When combined with a 2‐week low‐dose tacrolimus, the T‐5224 treatment markedly prolonged allograft survival to over 300 days, while the efficacy was indeterminate when transplanted islet allograft mass was reduced to 300. We conclude that the c‐Fos/AP‐1 inhibition by T‐5224 is a potentially attractive strategy for allogeneic PIT. Abstract : The authors provide evidence that the transcription factor activator protein‐1 plays a crucial role during rejection of pancreatic islet allografts in mice, and that the new inhibitor of activator protein‐1, T‐5224, is a potentially attractive candidate for immunosuppressive therapy after pancreatic islet transplantation.